The Current Evidence of Pulmonary Embolism Response Teams and Their Role in Future - Hobohm, Lukas; Farmakis, Ioannis T.; Duerschmied, Daniel; Keller, Karsten (Hämostaseologie, 2024)
Acute pulmonary embolism (PE) remains a critical medical condition requiring prompt and accurate management. The introduction and growing significance of pulmonary embolism response teams (PERT), also termed EXPERT-PE teams, signify a paradigm shift toward a collaborative, multidisciplinary approach in managing this complex entity. As the understanding of acute PE continues to evolve, PERTs stand as a linkage of optimized care, offering personalized and evidence-based management strategies for patients afflicted by this life-threatening condition. The evolving role of PERTs globally is evident in their increasing integration into the standard care pathways for acute PE. These teams have demonstrated benefits such as reducing time to diagnosis and treatment initiation, optimizing resource utilization, and improving patient outcomes.
Keywords: pulmonary embolism; PERT; catheter-directed treatment; ultrasound-accelerated thrombolysis; percutaneous thrombectomy